2012
DOI: 10.1103/physreva.86.022506
|View full text |Cite
|
Sign up to set email alerts
|

Ba+quadrupole polarizabilities: Theory versus experiment

Abstract: Three different measurements have been reported for the ground-state quadrupole polarizability in singly ionized barium (Ba + ) which disagree with each other. Our calculation of this quantity using the relativistic coupled-cluster method disagrees with two of the experimental values and is within the error bars of the other. We discuss the issues related to the accuracy of our calculations and emphasize the need for further experiments to measure the quadrupole polarizability for this state and/or the 5D stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The measured value is preliminary because cross checks for systematics are still ongoing. Our result agrees within 2σ with the most recent theoretical value τ D 5/2 = 29.8(3) s [6] and with the latest independent experimental value of τ D 5/2 = 31.2(9) s [15]. Figure 6 displays the time evolution of the measurements and the theory values for the lifetime of the 5d 2 D 5/2 state in a Ba + ion.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The measured value is preliminary because cross checks for systematics are still ongoing. Our result agrees within 2σ with the most recent theoretical value τ D 5/2 = 29.8(3) s [6] and with the latest independent experimental value of τ D 5/2 = 31.2(9) s [15]. Figure 6 displays the time evolution of the measurements and the theory values for the lifetime of the 5d 2 D 5/2 state in a Ba + ion.…”
Section: Discussionsupporting
confidence: 78%
“…The accurate determination of the transition probability of transitions in heavy alkali earth systems is an important step in the research program to measure Atomic Parity Violation (APV) in such systems [1][2][3][4][5][6][7][8][9]. In the research reported here, a single trapped Ba + ion has been investigated and the lifetime of its 5d 2 D 5/2 state has been measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accurate determination of the transition probability of transitions in heavy alkali earth systems is an important step in the research program to measure Atomic Parity Violation (APV) in such systems [1][2][3][4][5][6][7][8][9]. In the research reported here, a single trapped Ba + ion has been investigated and the lifetime of its 5d 2 D 5/2 state has been measured.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results are generally considered to be more reliable than the calculated results for many-electron atoms owing to the fact that ab initio evaluation of various physical quantities using many-body methods involve a number of approximations at different stages of the calculations. However, measurements from different experiments are not always in agreement and, in certain cases, large discrepancies between measurements and accurate calculations have been noted [12,13]. It is therefore essential to scrutinize the accuracies of both the experimental B and calculated B/Q results when determining values of Q from them.…”
mentioning
confidence: 97%